The Influence Of Financial Knowledge And E-Payment Awareness On Saving Behavior Of Accounting Students In Batam City - Caterine; Viola Syukrina E Janrosl (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
This study aims to examine the influence of financial knowledge and e-payment awareness on the saving behavior of accounting students in Batam City. The background of this research arises from the phenomenon of the increasing use of electronic payment systems among students, which may affect their financial management patterns and saving habits. This research employs a quantitative approach using a survey method. Primary data were collected through questionnaires distributed to accounting students at several universities in Batam City. The sampling technique applied is Slovin’s formula, with a total of 241 respondents. The independent variables in this study are financial knowledge (X₁) and e-payment awareness (X₂), while the dependent variable is saving behavior (Y). The research instrument was developed based on indicators relevant to financial literacy theory, technology awareness, and saving behavior, explained through the Theory of Planned Behavior (TPB) framework. Data analysis is planned to include validity tests, reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination (R²) using SPSS software. The results of this study are expected to provide theoretical contributions in enriching the literature on digital financial behavior and practical implications for higher education institutions in enhancing students’ financial literacy and digital payment awareness.